Greater China in an era of globalization - Guo, Sujian (ed.); GUo, Baogang (ed.) (New Delhi, 2010)
China's growth in the past few decades has been unprecedented, and continues to stay strong as it expands its influence around the globe. However, in many ways, the once insular China is still looking to find its footing as an international player in the globalization game. Greater China in an Era of Globalization looks at the success of China and its surrounding territories of Taiwan, Hong Kong, and Macau and asks the question "What is Chinese globalization?". The contributors in this volume look to answer this question by examining China's role both in its immediate sphere of influence and in the greater world. In doing so, the contributors argue that its push to globalize has had as much effect on the country itself, both politically and culturally, as it has had on the world. The contributors further the argument by analyzing China's influence on the rising nations in Africa and Latin America, before ending the book with a comparative analysis between it and the historic rise and fall of influence of its European counterparts.
Keywords: China-Foreign economic relations